Solution and solid state properties of Fe(III) complexes bearing N-ethyl-N-(2-aminoethyl)salicylaldiminate ligands - Martinho, Paulo N.
The effect of the phenolate ring derivatisation on the magnetic properties of Fe(III) complexes bearing Nethyl- N-(2-aminoethyl) salicylaldiminate ligands both in solid state and solution have been investigated. Two new complexes [Fe(3,5-Br-salEen)(2)]ClO4 center dot EtOH (5) and [Fe(3,5-Br-salEen)(2)]BPh4 center dot DMF (6) have been synthesised. SQUID magnetometry studies on these complexes showed that while complex 5 is in the low-spin (LS) state, complex 6 displays a gradual and incomplete spin crossover (SCO) transition over the temperature measured. Solution measurements on a series of six complexes e [Fe(salEen)2]ClO4 (1), [Fe(salEen)(2)]BPh4 center dot 0.5H(2)O (2), [Fe(5-Br-salEen)(2)]ClO4 (3), [Fe(5-Br-salEen)(2)]BPh4 center dot DMF (4), [Fe(3,5-Br-salEen)(2)]ClO4 center dot EtOH (5) and [Fe(3,5-Br-salEen)(2)]BPh4 center dot DMF (6) - were performed by UVevis and NMR spectroscopies and cyclic voltammetry. Solution studies show that the presence of electron withdrawing groups (bromine atoms) affect the electronic density at the phenolate ring, thus influencing the ligand field strength and the separation between the t(2g) and e(g)* energy levels. The presence of two bromide substituents at the phenolate ring has a more pronounced effect on the magnetic behaviour in solution than in the solid state, with both complexes 5 and 6 adopting preferentially the LS state. Electrochemical studies of complexes 1-6 reveal that the reduction of the metallic centres in the complexes with electron withdrawing groups is easier, with E-1/2 values of iron moving to more positive potentials with the number of bromide substituents at the phenolate ring. (C) 2013 Elsevier B. V. All rights reserved.